Gestão Social : conformação e Impactos de um programa de inclusão social na área da tecnologia - Santos, Ana Paula Ribeiro de Souza (2023)
This dissertation aims to analyze the conformations and impacts of the Inclusive Accelerator program, an inclusive education and training initiative through technology, developed by the articulation between academia and companies for the promotion of social justice, focusing on diversity and inclusion, thereby generating impact on society. This is in order to make known how the program has been shaping and impacting its different social actors in the period from 2018 to 2021 so as to reflect on the social management model that anchors it, as well as contribute with subsidies for its improvement. This research is defined as a case study and is therefore of mixed nature, descriptive and explanatory level, in the light of the historical-dialectical method. The analytical categories linked to the method which will enable an understanding of reality are: contradiction, totality, historicity and mediation; the explanatory categories being: social management, impact evaluation, accelerator and their social experiences. To achieve the research objective, empirical and documental research was conducted, whose data will be analysed using the textual discourse analysis technique of Moraes (2003). Interviews were conducted with managers/as of the companies and the university that make up the strategic team of the program; an online questionnaire was applied to the egresses of the program and 6 documents produced during the execution of the program in the period from 2019 to 2021 were analyzed. In this sense, the data indicate that programmes such as this one expand and consolidate access to social rights, position and execute the promotion of social justice whose purpose is the reduction of inequalities created in the ongoing capitalist system. Evidencing, thus, the alterations in the business models of companies in which the economic dimension is aligned with the social dimension. The main contradictions identified in this research are the inclusion-exclusion, collaboration-competition, impact-result relationships, which are being systematically overcome by the approach that society is the composition of all social actors, therefore people and organizations that live in it and that transforming these constitutive elements of social reality is of interest and necessity of all without exception. In this sense, promoting the articulation, precisely so that innovative alternatives are developed by organizations in the area of technology and other areas of knowledge that act as instruments for diversity, equity and inclusion in political, economic, social, technological, environmental and legal dimensions.